2014
DOI: 10.1159/000360806
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Remission of an Aggressive Sebaceous Carcinoma following Chemotherapy

Abstract: Sebaceous carcinoma (SC) is an uncommon neoplasm manifesting itself either in the eyelid or extraocularly in the head and neck area. Surgery is the standard of care. Irradiation is rarely proposed as monotherapy but is frequently administered as an adjuvant regimen following surgical resection. There is no known strategy concerning chemotherapeutic treatment in highly aggressive recurrent - or metastatic - forms of the disease. Our patient presented with an aggressive SC of the scalp recurring after multiple e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
(29 reference statements)
0
18
0
2
Order By: Relevance
“…However, there are isolated reports of using imaging to stage extraocular SC with magnetic resonance imaging (MRI) 36,37 and positron emission tomography scan (PET). 38 Some have recommended the use of CT scan 6 PET as an imaging modality for patients with palpable regional lymphadenopathy, nodal metastasis on SLNB, or primary lesions, demonstrating aggressive features clinically or histologically.…”
Section: Imagingmentioning
confidence: 99%
“…However, there are isolated reports of using imaging to stage extraocular SC with magnetic resonance imaging (MRI) 36,37 and positron emission tomography scan (PET). 38 Some have recommended the use of CT scan 6 PET as an imaging modality for patients with palpable regional lymphadenopathy, nodal metastasis on SLNB, or primary lesions, demonstrating aggressive features clinically or histologically.…”
Section: Imagingmentioning
confidence: 99%
“…Encouraged by these result, some studies suggested the possible role of systemic chemotherapy as neoadjuvant or adjuvant chemotherapy and illustrated positive result based on a few case reports [ 3 , 4 ]. However, most previously published reports were confined to only a few chemotherapeutic agents, especially 5-FU and platinum agents because these agents have been preferred in non-melanoma skin cancer and head and neck cancers [ 3 9 ]. However, when this regimen confronts resistance, patients ultimately require other systemic treatment option in the late of disease course.…”
Section: Discussionmentioning
confidence: 99%
“…First, we could confirm favorable response of capecitabine even after progression to 5-FU containing chemotherapy. To the best of our knowledge, only a few case reports have shown good responses to capecitabine or other fluorouracil agents (S-1) except 5-FU in sebaceous carcinoma [ 9 – 11 ]. Furthermore, in previous studies, capecitabine has been used in 5-FU naïve patients [ 10 ] and patients maintaining response to 5-FU [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy has been used for metastatic sebaceous gland carcinoma, but it is not effective (17,18). Accordingly, the study of sebaceous gland carcinoma-specific biomarkers is important for improving prognosis and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%